2008
DOI: 10.1590/s1519-69842008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects and landscape matrix use by a small mammal community in fragments of semideciduous submontane forest in Mato Grosso, Brazil

Abstract: A community of small mammals was studied in seasonal semideciduous submontane forest in the state of Mato Grosso, Brazil. This study evaluated the use of edge and matrix pasture, by different small mammal species. Overall, 31 areas were studied, with a total sampling effort of 33,800 trap x nights. Only seven of the 25 species captured in the study sites were able to use the pasture matrix; we classified these species as generalists. Fourteen species were found to be intermediate in habits, being able to use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
6
21
0
3
Order By: Relevance
“…A similar pattern was observed by Santos-Filho et al (2008), who recorded the highest richness and abundance in transects within forest fragments (300 m from the edge) compared to those located closer to the pasture (50 m from the edge) and at the edge of the forest. However, Pardini (2004) recorded a significantly higher species richness of small mammals at the edge of forest fragments in Atlantic Forest, while Malcolm (1997) Neotrop.,vol.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…A similar pattern was observed by Santos-Filho et al (2008), who recorded the highest richness and abundance in transects within forest fragments (300 m from the edge) compared to those located closer to the pasture (50 m from the edge) and at the edge of the forest. However, Pardini (2004) recorded a significantly higher species richness of small mammals at the edge of forest fragments in Atlantic Forest, while Malcolm (1997) Neotrop.,vol.…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, M. nudicaudatus was only captured in transects at least 250 m from the edge, which suggests they prefer forest habitats. Santos-Filho et al (2008) classified this species as "intermediate" in terms of habitat use, while the classified H. megacephalus as a "generalist", present throughout the forest, as observed in the present study. However, R. nitela, which was classified as an "intermediate" species by Santos-Filho et al (2008) was also captured at all distances from the edge in the present study, even though this is an arboreal species, which was likely undersampled in this study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In forest fragments in southwest Mato Grosso, this species was the second most captured, also occurring in forest fragments' edges, but never in pasture (Santos-Filho et al, 2008b); in the Amazon, however, some individuals were observed crossing short pasturelands (about 300 m) surrounded by forest (MNFS, unpublished data). Necromys lasiurus was captured only in Cerrado sensu stricto areas in Cerrado in Alter do Chão (Magnusson et al, 1995), however Ribeiro and Marinho-Filho (2005) captured that species in murundus fields (grassland) in the Brazilian Federal District.…”
Section: Discussionmentioning
confidence: 99%